Performance Effects of Shock Absorber and Spiral Springs Against Vertical Vehicle Expenses Weighing the Road Structure - Ka'ka, Simon; Andre H, Festo (Politeknik Negeri Ujung Pandang, 2020)
This study aims to examine more about the effect of vertical dynamic load of vehicles and changes in dimensional barriers on the road surface in its path. Experimentally this fluctuating load is replaced by a pneumatic force change based on the regulation of air pressure on the regulator. The deviations generated by the varying load work are measured by placing a proximity sensor along the spring movement. The amount of vertical load transformation reaches the road surface is measured by using Load cell. Characteristics of vertical dynamic vibration occurring due to several dimensional barriers, U (cm) obtained using mathematical modeling method with 2 DOF suspension system transfer function.Â The results showed a condition on the body and wheels of vehicles experienced a brief overshot for 0.14 seconds with deviation of 0.178 m. From the graph shows that the rate of deviation that occurs is large enough that Y2d = 1.03 m / s caused by a sudden shock that occurred on the wheels of the vehicle. This condition does not last long that is only duration t = 0.22 s, because the spring reaction force and shock absorber can absorb 25% vibration against the sprung and un-sprung vertical load of the vehicle.